(untitled) (R&E-SOURCE, 2026)
This study addresses the level of creativity among students in secondary vocational education and training programmes. The topic remains highly relevant and is increasingly being incorporated into the educational process by teachers. The research focuses on students’ creativity across various fields within these programmes, analysing differences and patterns in their creative abilities. Overall, the study examines the issue of creativity in adolescents within the context of vocational education.